2020
DOI: 10.1111/jace.17356
|View full text |Cite
|
Sign up to set email alerts
|

Highly tailorable electromechanical properties of auxetic piezoelectric ceramics with ultra‐low porosity

Abstract: Conventional porous piezoelectric ceramics can possess superior figures of merit only at very high values of porosity, leading to bad fragileness, small stiffness, low toughness, and the difficulty of polarization. To this end, this study for the first time shows that it is possible that the piezoelectric ceramic with ultra‐low porosity is capable of superior figures of merit based on the concept of auxetic piezoelectric ceramics. Owing to the ultra‐low porosity and auxetic effect, the auxetic piezoelectric ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…In this section, we will provide new insight on the relationship among piezoelectric strain and stress coefficients, figures of merit by introducing Poisson’s ratio to instead of some compliance coefficients. The crystal symmetry in common piezoelectric ceramics is 6mm or 4mm, but Tang et al 18 . indicated that the auxetic architecture may change the crystal symmetry into 2mm.…”
Section: New Insight On the Relationship Among Electromechanical Coefmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we will provide new insight on the relationship among piezoelectric strain and stress coefficients, figures of merit by introducing Poisson’s ratio to instead of some compliance coefficients. The crystal symmetry in common piezoelectric ceramics is 6mm or 4mm, but Tang et al 18 . indicated that the auxetic architecture may change the crystal symmetry into 2mm.…”
Section: New Insight On the Relationship Among Electromechanical Coefmentioning
confidence: 99%
“…This phenomenon can be attributed to the fact that the large deformation near the slits is undergone by PVDF, resulting in smaller stresses distributed in the PZT. Moreover, it has been demonstrated that auxetic porous structures have greater crack resistance than conventional porous structures 14,18,42,43 . Therefore, it is suggested that the auxetic architecture together with an appropriate amount of PVDF can effectively improve the deformability of piezoelectric materials, and ensure that the composite still has excellent electromechanical properties.…”
Section: Auxetic Piezoelectric Compositementioning
confidence: 99%
See 3 more Smart Citations